Sequelae of COVID-19 and the role of nursing in dealing with patients affected by this situation (Research, Society and Development, 2022)
Introduction: The new coronavirus was called COVID-19, which is an disease caused by the SARS-CoV-2 virus that can affect people in many ways, ranging from mild, moderate, or severe symptoms. In the front line, the nurse's role is focused on providing recovery and adaptation due to the restriction of some actions due to the illness. The main limitations pointed out are functional, motor, psychosocial, and spiritual. General objective: the objective of this article is to present the main sequelae caused by COVID-19, showing the importance of nursing in the confrontation of individuals affected by this situation. Method: the study is an integrative literature review, with the MEDLINE and SciELO databases, from August to December 2022. Results: articles in Portuguese and English were searched according to the eligibility criteria, 13 articles were evaluated. Discussion: Given the current scenario of covid we can take into consideration that the long-term sequelae are as symptoms that develop after 6 weeks or persist more than 6 weeks from the onset of symptoms of COVID-19.  The current WHO data, suggests that the time from onset to recovery for mild cases is approximately 2 weeks and in severe cases 3 to 6 weeks. It can also trigger pulmonary, cardiovascular, hepatic, and renal sequelae. Conclusion: The present study is of extreme importance for the knowledge about post-covid-19 sequelae, being necessary the creation of more scientific articles, accessible, in Portuguese language, enabling a wide understanding about the proposed subject